Out of the Closet: When Moral Identity and Protestant Work Ethic Improve Attitudes toward Advertising Featuring Same-Sex Couples. Issue 2 (15th March 2019) - El Hazzouri, Mohammed; Main, Kelley J.; Sinclair, Lisa
Abstract : This research examines how heterosexual consumers react to advertising featuring same-sex couples. Across three studies, we find that heterosexual consumers report higher levels of disgust in response to advertising featuring same-sex couples in comparison to mixed-sex couples, which results in more negative attitudes toward the advertisement and the advertised brand. We also find that moral-identity priming reduces disgust elicited by advertising featuring same-sex couples and improves attitudes toward the advertisement and the brand. However, we find that moral-identity priming is ineffective for consumers with high social dominance orientation. For these consumers, portraying same-sex couples as possessing Protestant work ethic traits decreases disgust and improves attitudes toward the advertisement and the brand.